Pengaruh Metode Explicit Instruction Terhadap Peningkatan Pengetahuan dan Sikap Dalam Penanganan Pertama Cedera - Suwandewi, Alit; Hiryadi, Hiryadi; Noor Khalilati; Izma Daud; Mariani; Hanafi Rizani (LPPM Universitas Sari Mulia, 2023)
The relatively high incidence of sports injuries, as well as the low level of knowledge and attitude in the first treatment of sports injuries, of course, need attention, because this can have a worse impact and more fatal pain. The purpose of this study was to determine the effect of health education using the Explicit Instruction method on increasing knowledge and attitudes in the first treatment of sports injuries at Al-Falah Putera Islamic Boarding School. This research is a pre-experimental type of One-Group Pretest-Posttest Design with the intervention of providing health education with the Explicit Instruction method. The number of respondents was 80 people who were taken using the Total Sampling technique. The data analysis used was the Wilcoxon test statistic. The results of the study at the level of knowledge and attitudes before and after both obtained a ρ value of 0.000 <α 0.05 in other words there was an effect of health education using the Explicit Instruction method on increasing the knowledge and attitudes of students. It is hoped that the results of this study will be able to become a good and useful basis for students in providing first aid when sports injuries occur. Islamic boarding schools are expected to be able to provide socialization on a regular basis and provide knowledge regarding the first proper handling of sports injuries.